A Clinical Study on Maternal and Perinatal Outcome of Oligohydramnios (Northern International Medical College Journal, 2022)
Background : Oligohydramnios is one of the pregnancy associated common complications facing by obstetrician which is associated with adverse maternal and perinatal outcome such as birth defects, miscarriage, intrauterine growth restriction, still birth, preterm birth, increased operative interference etc.Objective: To assess the impact of oligohydramnios on maternal and perinatal outcome.Methods: This cross-sectional descriptive study was conducted at Department of Obstetrics and Gynecology, BSMMU, Dhaka from October 2017 to March 2018.Total 50 patients were enrolled by purposive sampling method according to the inclusion and exclusion criteria. Clinical evidence of oligohydramnios was looked for & confirmed by ultrasonography (USG). Based on Amniotic fluid index (AFI)measurements patients were divided into two groups. Those who have AFI